ALTERED GLYCOSYLATION AND DISTRIBUTION OF THE β2 ADRENOCEPTOR IN HEART FAILURE. (21st November 2014) - Norman, R; Drinkhill, M; Deuchars, J; Calaghan, S
Abstract : Heart failure (HF) is a serious problem within the developed world. β-adrenergic receptors (βAR) undergo dramatic remodelling in HF characterised by a reduction in β1AR expression and decreased sympathetic responsiveness. Less is known about the consequences of HF for the β2AR, which is normally located predominantly within small invaginations of the membrane known as caveolae. Caveolar proteins are integral for the formation of caveolae; in the cardiac myocyte these include caveolin 1 (cav1) and caveolin 3 (cav3). Using an aortic banding model of HF in rat we looked at changes in expression of the β2AR and caveolar proteins, as well as changes in distribution of these proteins within the membrane. Progression of HF was measured by echocardiography. End-stage HF was defined as an ejection fraction <45%, as assessed by in-vivo haemodynamic measurements. Sham operated aged-matched rats were used as controls. There was no change in total expression of cav3, but a significant decrease in cav1 expression in HF (P<0.05, n=6) suggesting a change to the caveolar micro-domain. There was a trend for an increase in total β2AR and a significant increase (P<0.05) in β2AR located within caveolae-containing fractions in failing hearts. A high molecular weight band, consistent with the glycosylated form of the β2-AR, was also observed in HF but not controls; this was located solely within caveolae-containing fractions. These data show the first evidence for an increase in β2-AR glycosylation in HF which appears to direct the membrane localisation of the receptor and may impact on its signalling.